A rare pattern of lung metastasis of rectum adenocarcinoma. (12th February 2016) - Basara, Isil; Altay, Canan; Obuz, Funda; Balci, Pinar
Abstract: Lung is primary capillary filter of venous drainage for many organs. As a result of this, it is the most common metastasis site of extrapulmonary organ tumours. Cystic and cavitary forms of lung metastases are unusual. In evaluation of patients with these lesions benign and malignant lesions should be distinguished from each other. In this case report, we aimed to present computed tomography findings of an unusual cystic form of lung metastasis that is originated from rectum adenocarcinoma.